Recent land surface temperature patterns in Antarctica using satellite and reanalysis data. (November 2019) - Retamales-Muñoz, G.; Durán-Alarcón, C.; Mattar, C.
Abstract: Antarctica is among the most important regions when it comes to observing the effects of climate change. One important part of the variability of the land surface temperature (LST) observed on this continent is related to the sea surface temperature of the Tropical Pacific Ocean, which is associated with El Niño-Southern Oscillation (ENSO). This large-scale phenomenon is called tele-connection. In this study, we investigate the recent trends of LST in Antarctica over the last few decades and its relationship with one of the most intense El Niño events in 2015–2016. LST anomalies derived from satellite data (MODIS) and skin temperature from re-analysis (ERA-5 and ERA-Interim) were used, in addition to the Oceanic Niño Index (ONI) and Southern Annular Mode (SAM) time series. A non-parametric time series analysis was carried out to estimate LST trends over different zones of Antarctica. The results show a warming trend obtained from ERA-5 of about 0.9 K/decade in the interior of Antarctica, while MODIS showed the lowest temperature trends of −1 K/decade in East Antarctica. The analysis between LST and the SAM index shows a negative relationship in the extreme periods of ENSO 2015–2016, showing colder autumns and warmer springs than in previous years. These results aide in understanding the effects of extreme phases of ENSO on Antarctica, which are of great importance given the projection of more intense phases over the next century as foreseen in future scenarios of climate change. Highlights: Surface Temperature anomalies derived from satellite (MODIS) and re-analysis (ERA-5 and ERA-Interim) were used. The results show a warming trend obtained from ERA-5 of about 0.9 K/decade in the interior of Antarctica. Surface temperature and SAM index shows a negative relationship in the extreme periods of ENSO 2015–2016.